PRAKTIK NAZAR KOLEKTIF PADA MASYARAKAT KUNTU KABUPATEN KAMPAR - Oki Penri; Mustafid Mustafid (IAIN Padangsidimpuan, 2023)
Naghohgi tongue debt is a vow that is done simultaneously (collective vows), usually done because Allah protects the village of Kuntu from the disaster that has struck. So this article examines the Debt of Naghohgi's tongue in terms of Islamic law. And there are two problems in this research, namely how the practice of Naghohgi tongue debt in Kuntu village and how Islam sees it. The type of research is field research with a qualitative approach. The primary data sources are traditional leaders (link mamak), community leaders, religious scholars, and the community, while secondary data is from books, journal articles, and documents deemed necessary. Data collection techniques used interviews and documentation, while data analysis techniques used descriptive analytical techniques. The results of this study show that the implementation of the vows (Naghoghi Tongue Debt) carried out by the Kuntu Village community is a vow that is carried out jointly or collectively by the entire Kuntu community. This vow has been carried out since the ancestral times of the people of Kuntu Village and is very thick with a combination of cultural and religious values. Until now, it is still being carried out and developing. The vows were paid after an evaluation of the vows and an agreement between the Kuntu Village leadership, Ninik Mamak, and Alim Ulama. The vows were carried out for two days and two nights and were solemn and solemn. In terms of Islamic law, the vows (Naghoghi Tongue Debt) carried out by the people of Kuntu Village are not in accordance with the share, because one of the pillars of the vows, namely the subject or person making the vow, is not fulfilled. In worship, it is only considered valid if the pillars and conditions are met.